The Anthelmintic Potential of Ethyl Acetate Fraction Berenuk (Crescentia cujete L.) Fruit Against Mortality Haemonchus contortus In Vitro - Dyah Ajeng Suhita; Anwar Ma'ruf; Agus Sunarso; Eduardus Bimo Aksono; Dewa Ketut Meles (Journal of Parasite Science (JoPS), 2023)
This study aims to determine the anthelmintic potency of the ethyl acetate fraction of berenuk fruit (Crescentia cujete L.) on the mortality of the Haemonchus contortus worms in vitro. The method that was used in the research was a post-test only control group design. There were five treatments and each treatment was carried out in four repetitions. The sample used was twenty H. contortus in each treatment for all replications. Observation and recording of H. contortus mortality was carried out at 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60 minutes, and when all worms in the petri dish died. Data analysis using ANOVA, followed by Duncan’s Test and Probit analysis. The results showed that the ethyl acetate fraction of berenuk fruit had anthelmintic activity. The conclusion in this study is that the optimal concentration is found in the 0.5% ethyl acetate fraction concentration, the LC50 at each observation time successively is 1.39%; 0.97%; 0.70%; 0.48%; 0.39%; 0.34%; 0.31%; 0.28%; 0.27%; 0.26%; 0.25%; and 0.24%, while LT50 at a concentration of 0.125%; 0.25%; and 0.5% respectively are 1 hour 17 seconds, 41 minutes 42 seconds, and 20 minutes 58 seconds.